Redefining the diseases with reincarnation of 'Germ theory' - Ranabir Pal; Mitasha Singh; Rajesh Ranjan; Gautam Sarkar; Dharamvir Ranjan Bharati; Shrayan Pal (Al Ameen Medical College, 2017)
Chronic diseases or illnesses have a nick name 'non-communicable disease', where in spite of best efforts, apparently no microbial agent as cause of disease transmission could have been established till few years back. This confusion stemmed from the gaps in the natural history of those diseases, embedded in a) Absence of cause-effect knowledge, b) Multifactorial theories of morbidity c) Long latent periods, d) Indefinite as well as slow onsets, help damage to hosts long before the overt manifestations that may be irreversible or very difficult to reverse. With these vague ideas of non-communicable diseases we attempted to identify uncountable risk factors. So, primary and primordial prevention remained the mainstay in our armory in the name of 'First Contact Care'. Recent advancements and innovative wild thoughts (ignited by HIV thanks!) in the fields of microbiology as well as immunology have been able to establish role of microbes as causation of non-communicable diseases.